(untitled) (INCH : Journal of Infant and Child Healthcare, 2025)
Pneumonia is a respiratory tract infection that can cause toddlers death in the world. Transmission of Pneumoniae occurs through direct person-to-person contact via respiratory droplets. Pneumonia causes the alveoli to be filled with pus and fluid, which makes breathing painful and limited oxygen intake. One of the implementation to improve the airway of children with pneumonia is Pursed Lips Breathing therapy. The objective is to identify the application of pursed lip breathing therapy in children with pneumonia. This method was a descriptive case study approach with two subjects in the Payung Sekaki Community Health Center working area in April 2022. The results showed a change in the oxygenation status of subject I HR: 34 x/m RR: 90x/m Breathing Pattern: and subject II HR: 32x/m RR: 90x/m Breathing Pattern: Regular The conclusion is application of pursed lip breathing therapy can using by parent with pneumonia children in home.